1994
DOI: 10.1111/j.1439-0434.1994.tb00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pseudocercosporella herpotrichoides (Fron) Deighton var. herpotrichoides and var. acuformis on Wheat Plants Measured by ELISA

Abstract: Using the ELISA method, the development of Pseudocercosporella herpotrtchoides var. herpotrichoides and var. acuformis in a susceptible cultivar of winter wheat was compared under controlled and held conditions. In the greenhouse, var. acufornis grew less vigorously, was slower in penetrating the coleoptile and the successive leaf sheaths and in colonizing the stem tissue than var. herpotrichoides. In the field, these differences were confirmed on the last leaf sheaths and the stem. At ripening stage, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…herpotrichoides (presumed to be T. yallundae) isolates colonized hosts faster than var. acuformis (presumed to be T. acuformis) isolates (Poupard et al, 1994). The results of the glasshouse test indicate that the relationship between fungal DNA content and visual disease is also worthy of further investigation, as the results presented here suggest that the DNA content of wheat seedlings with similar disease scores might differ greatly depending on the species of Tapesia involved.…”
Section: Discussionmentioning
confidence: 75%
“…herpotrichoides (presumed to be T. yallundae) isolates colonized hosts faster than var. acuformis (presumed to be T. acuformis) isolates (Poupard et al, 1994). The results of the glasshouse test indicate that the relationship between fungal DNA content and visual disease is also worthy of further investigation, as the results presented here suggest that the DNA content of wheat seedlings with similar disease scores might differ greatly depending on the species of Tapesia involved.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, use of chronological time (e.g. days after sowing) to describe eyespot development (Fitt et al ., 1988; Goulds & Fitt, 1990a, 1991; Poupard et al ., 1994) is less accurate, because there may be prolonged periods during winter in the UK when temperatures are too low for organisms to grow. A base temperature of 0°C for pathogen growth was assumed throughout these studies, because no detailed studies have been done in planta to examine whether OY and OA grow at ambient temperatures below 0°C, as has been done with Mycosphaerella graminicola infecting wheat leaves (Lovell et al ., 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…Thermal time (accumulated °C days) provides a more appropriate scale than a scale based on days from sowing, and has previously proved helpful in describing the progress of foliar disease of cereals (Beresford & Royle, 1988; Lovell et al ., 2004a). However, only days after sowing has previously been used as a measure to compare progress in stem‐base tissues of eyespot caused by OY and OA (Goulds & Fitt, 1990a; Poupard et al ., 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The method was applied to study the stability of eyespot response measured by ELISA in 20 wheat cultivars studied in six environments (Lind et al. 1994), relative rates of O. yallundae and O. acuformis development in wheat (Poupard et al. 1994), variation in eyespot response in Pch1 ‐carrying genotypes (Lind 1999) and quantitative inheritance of eyespot resistance in diallel crosses (Lind 2000).…”
Section: Methods For the Assessment Of Eyespot Resistancementioning
confidence: 99%
“…Differential response to the two Oculimacula species is a related subject more often discussed in recent publications. Poupard et al. (1994) showed that cultivars with Pch1 (‘Roazon’ and ‘Rendezvous’) carried much less O. acuformis material as measured by ELISA than O. yallundae material, in the same experimental field and the same environmental conditions where plants had been inoculated separately with isolates of the two species.…”
Section: Durability Of Eyespot Resistance Genesmentioning
confidence: 99%